Directed-evolution approach to empower EGFR targeting for immunotherapy - Bunyarit Meksiriporn; Jamie B. Spangler (My University, 2024)
Advances in directed-evolution technologies are enabling new strategies to isolate binding proteins that recognize disease-associated states of a target protein. In this issue of Cell Reports Methods, Dobersberger et al. devised a yeast display-based selection scheme to discover proteins that engage the cancer-associated activated state of a receptor to enable design of safe and effective immunotherapies. Advances in directed-evolution technologies are enabling new strategies to isolate binding proteins that recognize disease-associated states of a target protein. In this issue of Cell Reports Methods, Dobersberger et al. devised a yeast display-based selection scheme to discover proteins that engage the cancer-associated activated state of a receptor to enable design of safe and effective immunotherapies. Chimeric antigen receptor (CAR) T cell therapy has emerged as a clinically effective adoptive cell transfer approach that utilizes a patient's genetically modified T cells to express CARs that specifically recognize tumor-associated antigens. CAR T cells are composed of three main components: (1) extracellular binding domain, (2) transmembrane domain, and (3) intracellular T cell signaling/costimulatory domains. The extracellular binding domain on CAR T cells recognizes antigens expressed on the tumor cell surface in a major histocompatibility complex (MHC)-independent manner, which in turn stimulates T cells to kill cancer cells.1Yu S. Li A. Liu Q. Li T. Yuan X. Han X. Wu K. Chimeric antigen receptor T cells: a novel therapy for solid tumors.J. Hematol. Oncol. 2017; 10: 78https://doi.org/10.1186/s13045-017-0444-9Crossref PubMed Scopus (227) Google Scholar First-generation CARs contain only the signaling domains of CD3 zeta chain (CD3ζ) or Fc γ receptors (FcRγ) within the intracellular domain, which induces transient T cell activation.1Yu S. Li A. Liu Q. Li T. Yuan X. Han X. Wu K. Chimeric antigen receptor T cells: a novel therapy for solid tumors.J. Hematol. Oncol. 2017; 10: 78https://doi.org/10.1186/s13045-017-0444-9Crossref PubMed Scopus (227) Google Scholar Second- and third-generation CARs incorporate one of these activation domains in addition to one or two costimulatory receptor signaling domains (e.g., CD28, 4-1BB, OX40), respectively. Addition of costimulatory domains supports prolonged T cell activation and cytokine secretion, which bolsters antitumor activity and leads to improved treatment outcomes. Given the promising success of CAR T cell therapy in preclinical models and human clinical trials, the US Food and Drug Administration (FDA) has approved six CAR T cell therapies to date in hematological cancer indications, including acute lymphoblastic leukemia (ALL), B cell lymphoma, follicular lymphoma (FL), mantle cell lymphoma, and multiple myeloma (MM).2Sengsayadeth S. Savani B.N. Oluwole O. Dholaria B. Overview of approved CAR-T therapies, ongoing clinical trials, and its impact on clinical practice.EJHaem. 2022; 3: 6-10https://doi.org/10.1002/jha2.338Crossref PubMed Google Scholar Although CAR T cell therapies have been transformative in treating hematological malignancies, performance has been disappointing in solid tumor malignancies due to several factors, including lack of appropriate tumor-specific markers, limitations in tumor penetration, and immunosuppressive activities within the tumor microenvironment. Epidermal growth factor receptor (EGFR) is a well-studied tumor-associated antigen that is ubiquitously expressed in healthy tissue throughout the body but often aberrantly upregulated in cancer. There are two classes of FDA-approved EGFR-targeting anti-cancer agents: anti-EGFR monoclonal antibodies (cetuximab, panitumumab, necitumumab, and nimotuzumab) and small molecule tyrosine kinase inhibitors (TKIs; gefitinib, erlotinib, and osimertinib). Despite their efficacy as frontline treatments for several cancer types, these agents can lead to dermatologic toxicities due to their interaction with both tumor cells and healthy tissue.3Lacouture M.E. Anadkat M. Jatoi A. Garawin T. Bohac C. Mitchell E. Dermatologic Toxicity Occurring During Anti-EGFR Monoclonal Inhibitor Therapy in Patients With Metastatic Colorectal Cancer: A Systematic Review.Clin. Colorectal Cancer. 2018; 17: 85-96https://doi.org/10.1016/j.clcc.2017.12.004Abstract Full Text Full Text PDF PubMed Scopus (55) Google Scholar There have also been intensive efforts to develop bispecific T cell engagers (BiTEs) that incorporate anti-EGFR antibody domains to colocalize T cells with tumor cells for efficient tumor clearance, but these approaches also face severe toxicity challenges.4Goebeler M.-E. Bargou R.C. T cell-engaging therapies - BiTEs and beyond.Nat. Rev. Clin. Oncol. 2020; 17: 418-434https://doi.org/10.1038/s41571-020-0347-5Crossref PubMed Scopus (276) Google Scholar CAR T cell therapies targeting EGFR have been investigated in both preclinical and clinical contexts; however, to date, these therapies have demonstrated limited clinical efficacy.5Albert C.M. Pinto N.R. Taylor M. Wilson A. Rawlings-Rhea S. Mgebroff S. Brown C. Lindgren C. Huang W. Seidel K. et al.STRIvE-01: Phase I study of EGFR806 CAR T-cell immunotherapy for recurrent/refractory solid tumors in children and young adults.J. Clin. Orthod. 2022; 40: 2541https://doi.org/10.1200/JCO.2022.40.16_suppl.2541Crossref Google Scholar Moreover, again due to the universal expression of the receptor, EGFR-targeted CAR T cell therapies can cause severe adverse side effects due to on-target/off-tumor toxicities. To improve the tumor specificity of EGFR-targeted therapies, there are efforts to target EGFR variant III (EGFRvIII), a truncated and constitutively active form of EGFR that manifests in certain tumor types, including glioblastoma.6An Z. Aksoy O. Zheng T. Fan Q.-W. Weiss W.A. Epidermal growth factor receptor and EGFRvIII in glioblastoma: signaling pathways and targeted therapies.Oncogene. 2018; 37: 1561-1575https://doi.org/10.1038/s41388-017-0045-7Crossref PubMed Scopus (356) Google Scholar EGFRvIII serves as a promising target for monoclonal antibody drugs, BiTEs, and CAR T cell therapies since its expression is restricted to tumor tissue. However, only certain cancer types express EGFRvIII, limiting the scope of this therapeutic strategy. To create a broadly applicable EGFR-targeted therapy with improved selectivity, safety, and efficacy, Dobersberger et al.7Dobersberger M. Sumesgutner D. Zajc C.U. Salzer B. Laurent E. Emminger D. Sylvander E. Lehner E. Teufl M. Seigner J. et al.An engineering strategy to target activated EGFR with CAR T cells.Cell Rep. Methods. 2024; 4: ◼https://doi.org/10.1016/j.crmeth.2024.100728Abstract Full Text Full Text PDF Scopus (0) Google Scholar sought to engineer an anti-EGFR CAR that specifically targets the activated form of the receptor (Figure 1A), which is highly prevalent in tumor but not healthy tissue. To this end, the investigators designed an engineering workflow for the isolation of CARs incorporating variants of the highly stable protein reduced charge Sso7d (rcSso7d) that selectively recognize the activated state of EGFR. The researchers used two previously established yeast surface displayed libraries8Traxlmayr M.W. Kiefer J.D. Srinivas R.R. Lobner E. Tisdale A.W. Mehta N.K. Yang N.J. Tidor B. Wittrup K.D. Strong Enrichment of Aromatic Residues in Binding Sites from a Charge-neutralized Hyperthermostable Sso7d Scaffold Library.J. Biol. Chem. 2016; 291: 22496-22508https://doi.org/10.1074/jbc.M116.741314Abstract Full Text Full Text PDF PubMed Scopus (40) Google Scholar based on the small, thermostable, and well-expressed rcSso7d protein.9Gera N. Hussain M. Wright R.C. Rao B.M. Highly stable binding proteins derived from the hyperthermophilic Sso7d scaffold.J. Mol. Biol. 2011; 409: 601-616https://doi.org/10.1016/j.jmb.2011.04.020Crossref PubMed Scopus (74) Google Scholar To skew binding toward the activated form of EGFR, the displayed libraries were selected against EGFR fused to the human immunoglobulin G1 (IgG1) Fc domain (forming a dimeric molecule termed EGFR-Fc) in the presence of ligand (either EGF or transforming growth factor α [TGF-α]). Additionally, a customized screening strategy was deployed that alternated negative selections against EGFR-Fc in the absence of ligands with positive selections against EGFR-Fc in the presence of ligands (Figure 1B), as well as interspersed rounds of error-prone mutagenesis. This strategy, implemented over multiple rounds of magnetic-activated cell sorting and fluorescence-activated cell sorting, led to enrichment of binders that recognized the activated conformation of EGFR, irrespective of ligand. After 10 rounds of selection, 7 EGFR-targeted rcSso7d variants were isolated from the enriched libraries that preferentially bound to receptor in the presence of ligand. An additional rcSso7d variant isolated from a previous study8Traxlmayr M.W. Kiefer J.D. Srinivas R.R. Lobner E. Tisdale A.W. Mehta N.K. Yang N.J. Tidor B. Wittrup K.D. Strong Enrichment of Aromatic Residues in Binding Sites from a Charge-neutralized Hyperthermostable Sso7d Scaffold Library.J. Biol. Chem. 2016; 291: 22496-22508https://doi.org/10.1074/jbc.M116.741314Abstract Full Text Full Text PDF PubMed Scopus (40) Google Scholar was also included, as it showed improved EGFR binding in the presence of EGF even though it was selected in the absence of ligand. Yeast surface-binding studies distinguished the rcSs07d variants into two categories based on ligand dependencies: (1) binders that selectively recognized EGFR only in the presence of EGF and (2) binders with background binding to EGFR but preferential recognition of the receptor in the presence of ligand (either EGF or TGF-α). Binding of the recombinant rcSso7d proteins to human tumor cells was studied for multiple cancer cell lines with EGFR expression levels ranging from ∼104 to 5 × 105 receptors/cell. In line with yeast surface binding studies, the two binders from category (1) exclusively bound EGFR-expressing cancer cell lines in the presence of EGF. Strikingly, many of the binders from category (2) showed significantly more ligand selectivity in cancer cell lines compared to what was observed in yeast cells. Moreover, none of the selected clones bound to EGFR-negative human cell lines or healthy primary human dermal fibroblasts (HDFs) in the absence of ligands, although low levels of binding were detected in HDFs upon addition of EGF. Encouraged by these selective binding results, the investigators sought to validate the functionality of their four most promising binders using a Jurkat Nur77 reporter cell line, engineered to fluoresce in response to T cell receptor signaling. rcSso7d variants were incorporated into second-generation CARs containing CD3ζ and CD28 or 4-1BB costimulatory domains, which were then transduced into Jurkat Nur77 reporter cells (Figure 1C). Consistent with binding studies, CAR T cells containing the category (1) clone ActE_21 exhibited highly selective activation when cultured with EGFR-expressing tumor cells in the presence versus the absence of EGF. CAR T cells containing the category (2) clones ActE_20- and ActE_29 showed greater activation when cultured with EGFR-expressing tumor cells in the presence versus absence of ligands. The activities of rcSso7d variant-based CARs were further validated in primary human T cells, using second-generation CARs containing CD3ζ and CD28 costimulatory domains. Aligned with the findings in Jurkat Nur77 reporter cells, ActE_21-based CAR T cells secreted interferon (IFN)-γ upon co-culture with EGFR-expressing tumor cells only when EGF was present. Also, in agreement with reporter cell findings, ActE_20- and ActE_29-based CAR T cells secreted much higher levels of IFN-γ upon co-culture with EGFR-expressing tumor cells in the presence versus the absence of EGFR ligands. Finally, the investigators demonstrated the activity of their CAR T cells in cytotoxicity assays against EGFR-expressing tumor cells (Figure 1C). Whereas the ActE_21-based CAR T cells demonstrated specific tumor cell killing only in the presence of EGF, the ActE_20- and ActE_29-based CAR T cells indiscriminately killed EGFR-expressing cancer cells in the presence or absence of ligand. Collectively, the engineered rcSso7d variants discovered in this study demonstrated selectivity for the liganded state of EGFR, and the most promising variant (ActE_21) was successfully exploited to generate CAR T cells that specifically killed EGFR-expressing tumor cells in the presence of the EGF ligand. The engineering strategy described herein introduces an innovative workflow to isolate binders that recognize specific states of their target proteins. Previous studies have selected for molecules that stabilize specific protein conformations for various purposes, including crystallography,10Rasmussen S.G.F. DeVree B.T. Zou Y. Kruse A.C. Chung K.Y. Kobilka T.S. Thian F.S. Chae P.S. Pardon E. Calinski D. et al.Crystal structure of the β2 adrenergic receptor–Gs protein complex.Nature. 2011; 477: 549-555https://doi.org/10.1038/nature10361Crossref PubMed Scopus (2430) Google Scholar induction of dimerization,11Spangler J.B. Moraga I. Jude K.M. Savvides C.S. Garcia K.C. A strategy for the selection of monovalent antibodies that span protein dimer interfaces.J. Biol. Chem. 2019; 294: 13876-13886https://doi.org/10.1074/jbc.RA119.009213Abstract Full Text Full Text PDF PubMed Scopus (13) Google Scholar or agonism.12Adams R. Burnley R.J. Valenzano C.R. Qureshi O. Doyle C. Lumb S. Del Carmen Lopez M. Griffin R. McMillan D. Taylor R.D. et al.Discovery of a junctional epitope antibody that stabilizes IL-6 and gp80 protein:protein interaction and modulates its downstream signaling.Sci. Rep. 2017; 737716https://doi.org/10.1038/srep37716Crossref Scopus (36) Google Scholar In each case, the choice of how to present the selection target was critical in order to pressure the selection in the intended direction. Dobersberger et al.7Dobersberger M. Sumesgutner D. Zajc C.U. Salzer B. Laurent E. Emminger D. Sylvander E. Lehner E. Teufl M. Seigner J. et al.An engineering strategy to target activated EGFR with CAR T cells.Cell Rep. Methods. 2024; 4: ◼https://doi.org/10.1016/j.crmeth.2024.100728Abstract Full Text Full Text PDF Scopus (0) Google Scholar sought to evolve binders that recognize the activated state of the receptor by performing selections in the presence of ligands. An important consideration for such selections is the affinity of the ligand/receptor interaction. In this case, the very tight (single-digit nanomolar-range) binding of both EGF and TGF-α ensured that the target complex would stay together for the duration of the selection, and the use of supersaturating amounts of ligands in the selections further ensured that EGFR would be presented in the activated state. Moreover, the dimeric format of EGFR-Fc facilitated presentation of the active 2:2 ligand:receptor complex. In cases where the ligand/receptor interaction is weaker, affinity maturation strategies could be implemented to strengthen this interaction prior to selections. Another important consideration in this evolutionary workflow was the inclusion of both negative selections against the unbound inactive EGFR and positive selections against the ligand-bound activated receptor. Additional counterselections against the ligands themselves could also potentially be incorporated into the workflow to further enrich for binders that engage the receptor. It should also be noted that some of the newly discovered binders may be recognizing a composite interface between EGF and EGFR, and it will be interesting to explore the unique binding geometries of these rcSso7d variants in future studies. The discovery of one binder (ActE_21) with striking selectivity for EGFR binding in the presence of EGF represents a translationally promising engineering feat. Despite the attrition that emerged from various stages of the selection process, this study offers compelling proof of concept for the notion of identifying binding moieties that recognize disease-specific protein conformations. In the case of EGFR, this result is highly enabling, as this receptor is overexpressed and dysregulated across multiple cancer types, yet its value as a target for immunotherapy modalities such as BiTEs and CAR T cells has been limited by its ubiquitous expression throughout the body.4Goebeler M.-E. Bargou R.C. T cell-engaging therapies - BiTEs and beyond.Nat. Rev. Clin. Oncol. 2020; 17: 418-434https://doi.org/10.1038/s41571-020-0347-5Crossref PubMed Scopus (276) Google Scholar,5Albert C.M. Pinto N.R. Taylor M. Wilson A. Rawlings-Rhea S. Mgebroff S. Brown C. Lindgren C. Huang W. Seidel K. et al.STRIvE-01: Phase I study of EGFR806 CAR T-cell immunotherapy for recurrent/refractory solid tumors in children and young adults.J. Clin. Orthod. 2022; 40: 2541https://doi.org/10.1200/JCO.2022.40.16_suppl.2541Crossref Google Scholar ActE_21 and other similarly biased proteins open up new opportunities to improve the efficacy and safety of cancer treatments, and analogous selection campaigns can be deployed to target proteins that exhibit distinct conformational changes in other disease conditions, such as neurodegenerative disorders. Overall, the work by Dobersberger et al.7Dobersberger M. Sumesgutner D. Zajc C.U. Salzer B. Laurent E. Emminger D. Sylvander E. Lehner E. Teufl M. Seigner J. et al.An engineering strategy to target activated EGFR with CAR T cells.Cell Rep. Methods. 2024; 4: ◼https://doi.org/10.1016/j.crmeth.2024.100728Abstract Full Text Full Text PDF Scopus (0) Google Scholar presents directed-evolution methodologies that will empower functionally biased selections to focus and facilitate the discovery of targeted interventions for a vast array of research and therapeutic applications. We acknowledge funding from the National Science Foundation (CAREER award 2143160 to J.B.S.). Figure was created using BioRender (https://biorender.com). The authors declare no competing interests. An engineering strategy to target activated EGFR with CAR T cellsDobersberger et al.Cell Reports MethodsMarch 15, 2024In BriefEGFR is often found to be constitutively activated in human cancer. Dobersberger et al. develop an engineering strategy for the generation of binding domains specifically recognizing ligand-activated EGFR. Incorporation of these binders into CAR molecules allows for specific targeting of the activated state of EGFR with CAR T cells. Full-Text PDF Open Access
Keywords: Cancer Immunotherapy; CAR-T cell therapy research